Triple-Row Modification of Knotless Speed Bridge Technique for Rotator Cuff Repair - Roger V. Ostrander MD; Skyler T. Hoelscher MD; Eric A. Branch MD; Reece Vesperman MD; Cooper Williams; Garrett Flynn (Video Journal of Sports Medicine)
Background: Rotator cuff pathology is the leading cause of shoulder-related disability, with approximately 250,000 rotator cuff procedures performed annually in the United States. Large rotator cuff tears can disrupt the force-couple of the shoulder, leading to loss of active motion, increased pain, and decreased function. Indications: Arthroscopic rotator cuff repair has become the predominant surgical approach. Double-row constructs, such as the suture bridge technique (transosseous equivalent), have been developed to improve repair anatomy and fixation strength. However, despite these technical advances, retear rates remain high, especially for larger tears. Technique Description: The following technique demonstrates the triple-row modification of the knotless speed bridge repair for rotator cuff tears. The triple-row modification of the suture bridge technique uses a third row of fixation placed between the typical medial and lateral rows. Results: The goal of the middle-row anchor is to reduce the cuff back into its anatomic position before tying the medial row anchors and can be easily incorporated into the standard speed bridge construct. Discussion/Conclusion: The triple-row modification of the knotless speed bridge repair offers a more anatomic repair with improved rotator cuff footprint contact area and an extra point of fixation. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.